Student access to the curriculum in an age of performativity and accountability: an examination of policy enactment. Issue 2 (3rd March 2020) - Harris, Richard; Courtney, Louise; Ul-Abadin, Zain; Burn, Katharine
ABSTRACT: The curriculum is often the target of reform and governments use a range of accountability measures to ensure compliance. This paper examines the decisions schools in England make regarding history provision, in a period of curriculum change, and the potential consequences of these decisions. Drawing on a large, longitudinal data set, of primary and secondary material, the study examines the relationship between the number of students entered for public examination in history in England and a range of situated and material factors. The data suggest that particular measures of accountability are effective in shaping school decision-making, but the type of school, socio-economic nature of the school intake, and students' prior attainment are also important factors in understanding the decisions made. This does result in an inequitable access to history education; this inequity exists between different types of schools and socio-economic areas, and is also evident within schools where students with low prior attainment are less likely to be allowed to study history.